(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The University of New Hampshire (UNH) and XFlow Energy jointly designed and built a 1-meter rotor diameter axial-flow turbine (AFT) test bed for use in the UNH towing tank as part of the Atlantic Marine Energy Center’s (AMEC) test infrastructure improvement initiative. The AMEC-UNH AFT test bed fills an infrastructure gap in tidal energy testing facilities at UNH and serves as a scale model for the US Department of Energy’s 2.5-meter Open-Source Tidal Energy Converter (OSTEC) turbine test bed at the AMEC-UNH tidal energy test site on the Piscataqua River. The combination of rotor size and achievable towing speeds permits testing in a regime where turbine performance becomes independent of Reynolds number effects, while also minimizing blockage. These design considerations support the primary purpose of the AFT test bed to facilitate experiments that test and improve AFT designs and provide data for numerical model verification and validation (V&V) to the marine energy industry. Potential research applications of the test bed include testing different blade designs and materials, quantifying the effects of turbulence, cavitation, yaw, and upstream obstacles on turbine power performance and loading, testing under combined current and waves, determining wake characteristics downstream of the device, and conducting scale tests of reference model turbines. The AMEC-UNH AFT test bed is instrumented with two custom load cells that measure rotor thrust and torque and blade root bending moments, respectively. Additionally, the test bed features a servomotor and drive for precise rotor speed control and tip-speed ratio selection. Together, these measurements are used to calculate performance coefficients and structural loading for a 1-m scale turbine. Baseline performance studies were conducted over a full range of tip-speed ratios (λ = 1−8) and current velocities (U∞ = 0.4−2 [ms−1]) for a rotor with modified MHKF1 hydrofoil family geometry. A detailed uncertainty analysis of the test bed’s instrumentation was also conducted to determine any limitations of the system for future experiments. The results of this uncertainty analysis indicate that measurement uncertainties predominantly originate from systematic error inherent to the thrust and torque and blade root bending moment load cells and that random error is comparatively low. As such, the data and results from the test bed are repeatable, increasing confidence in their accuracy. The derived quantities of interest from UNH’s towing tank experiments, including power performance coefficients and blade root bending moments, are used to validate an OpenFAST model. This work serves as an initial step to develop an integrated numerical-physical modeling methodology and framework that enables improved marine turbine performance assessments to refine turbine designs and de-risk deployments, specifically the design and deployment of the OSTEC turbine.